The Ecumenism in the era of social media: the challenge of facing digital theological polarization in building church fellowship - Mariesa Theofanny Pattiruhu; Florence Peea (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The development of social media has transformed patterns of religious communication and created new spaces for the formation of digital theology within church life. On the one hand, social media provides opportunities to expand dialogue, strengthen relationships, and foster cooperation among Christians. On the other hand, digital spaces have also generated theological polarization characterized by the reinforcement of group identities, polemical communication, and the weakening of interdenominational dialogue. This study aims to analyze the challenges posed by digital theological polarization to church unity and to examine the relevance of ecumenical principles and koinonia as theological foundations for fostering unity in the social media era. The research employs a qualitative method with a literature study approach through the analysis of theological literature and relevant digital religion studies. The findings indicate that digital theological polarization is driven by unrestricted access to information, the homogenization of digital communities, confrontational communication cultures, and the rapid dissemination of religious narratives through social media. Its impacts include not only increasing theological conflicts but also weakening relationships, dialogue, and cooperation among Christians. To address these challenges, churches need to develop ecumenical strategies that include strengthening Christian communication ethics, enhancing theological and digital literacy, promoting interdenominational dialogue, encouraging digital collaboration among churches, and cultivating a spirituality of koinonia. Through these efforts, social media can be transformed into a medium that supports church unity and strengthens Christian witness in the digital public sphere.